2016
DOI: 10.1016/j.socscimed.2016.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Regional inequalities in self-rated health in Russia: What is the role of social and economic capital?

Abstract: Using the data from the European Social Survey (round 6, 2012), this article studies regional inequalities in self-rated health in Russia and examines the role that socio-demographic factors and economic and social capital play in these differences. Also, the regional variation in the determinants of self-rated health is analysed. The article argues that there are considerable and statistically significant unadjusted differences in self-rated health across Russian Federal Districts. We elaborated these differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…With limited budgetary resources, the social sphere is of lower priority for the Russian than other sectors. Ongoing reduction of healthcare expenditures contributes to the growth of regional inequalities (Grigoriev et al, 2014;Lyytikäinen and Kemppainen, 2016). It is not surprising that the planned figures for life expectancy are constantly being adjusted downwards.…”
Section: Discussion and Policy Implicat Ionsmentioning
confidence: 99%
“…With limited budgetary resources, the social sphere is of lower priority for the Russian than other sectors. Ongoing reduction of healthcare expenditures contributes to the growth of regional inequalities (Grigoriev et al, 2014;Lyytikäinen and Kemppainen, 2016). It is not surprising that the planned figures for life expectancy are constantly being adjusted downwards.…”
Section: Discussion and Policy Implicat Ionsmentioning
confidence: 99%
“…", accompanied by a five-point response scale, ranging from "good" to "poor". Following a typical practice, the variable was dichotomised, and the categories "good" and "fairly good" were combined to indicate the state of good subjective health (e.g., Ahnquist et al 2012;Carlson 2016;Lyytikäinen and Kemppainen 2016). This choice of the cut-off reflects Carlson's (2016) argument that health is a positive state instead of a mere absence of illness, where the respondents who choose the "average" mid-option are assumed to "experience some kind of health problem" (ibid., 4).…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies have shown that there is an association between low levels of SES and poor health outcomes 1 : and this association has been noted both at the individual level and the ecological level. 26 Yet, despite this well-established association, traditional measures of SES do not capture the differential experience of SES that results from the disparate demands on financial resources across households. 7–8 Therefore, many researchers have called for an expanded conceptualization and operationalization of SES to include other indicators such as wealth, debt, and hardship.…”
Section: Introductionmentioning
confidence: 99%